COBIT 5: INFORMATION TECHNOLOGY AUDIT IN RELIGIOUS COURTS - Firdaus -; Aggy Pramana Gusman; Harkamsyah Andrianof (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Information technology in an organization is very important to support organizational assets. An information technology audit needs to be carried out to determine the level of suitability of the current situation with the expected target. This study aims to manage audit findings and produce recommendations for improvement and sustainable management. This study uses the COBIT 5 framework. The chosen domain is DSS (Deliver, Service, and Support). The results of the study show that the average scale is 3.67 with a capability level of 4. The recommendations that appear can be used as a reference for achieving information technology targets at the Padang Class I A Religious Court.